A Giant Tunable Piezoelectric Performance in Two‐dimensional In2Se3 via Interface Engineering - Shuoguo Yuan; Yiming Zhang; Minzhi Dai; Yancong Chen; Haiyan Yu; Zengsheng Ma; Weng Fu Io; Xin Luo; Pengfei Hou; Jianhua Hao (Advanced Electronic Materials, 2024)
Abstract Two‐dimensional (2D) layered piezoelectric materials have attracted enormous interest, which leads to wide applications in stretchable electronic, energy and biomedicine. The piezoelectric properties of 2D materials are mainly modulated by strain, thickness, defect engineering and stacked structure. However, the tunability of piezoelectric properties is typically limited by the small variation within one order of magnitude. It is challenging to obtain high tunable piezoelectric properties of 2D materials. Here, this study reports that the out‐of‐plane piezoelectric properties of 2D van der Waals In2Se3 are significantly manipulated using interface engineering. The variation value of piezoelectric properties is above two orders of magnitude, giving rise to the highest variation value in the 2D piezoelectric materials system. In particular, the 2D materials In2Se3 can be directly fabricated onto silicon substrate, which suggests its compatibility with the state‐of‐the‐art silicon semiconductor technology. Combining the experimental and computational results, this study reveals that the ultrahigh tunable piezoelectric properties result from the interface charge transfer effect. The work opens the door to design and modulate the unprecedented applications of atomic‐scale smart and multifunctional devices.